A review on family caregiving challenges in Malaysia - Chan, Siaw Leng; Matsah, Nurul Syahmah Binti; Yusuf, Aidatul Ashya Binti; Khaidir, Anis Syahmina Binti Mohd; Hamdan, Nur Haiza Binti; Kamizi, Zayti Nurallya Binti (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
Family caregiving often involves family members, relatives, and partners with whom the patients have a personal relationship to assist the care. The roles of caregivers are extensive and require a lot of effort, time, and commitment. These demands might possibly affect the life of caregivers. This paper aims to identify how family caregiving in Malaysia might have jeopardized the caregiver's life. A systematic approach analysis was utilized in this study while including seventeen articles. The exclusion criteria were articles published in reputable journals containing the research topic with the keywords "burden", "finance", and "stress". The focus of the study was on the impact, mental health status, quality of life, and burden related to caregivers in Malaysia. The articles were categorized into four themes: mental health status, impact, quality of life, and burden towards family caregiving in Malaysia. The results showed that in the theme of mental health status, caregivers experienced significant stress and one of the factors is the family's lack of knowledge in dealing with stress. Meanwhile, in terms of impact, the results indicated that caregivers experienced negative impacts on their emotions and health. In the quality of life theme, the results presented that family caregiving had a positive impact on increasing bonding between patients and caregivers. The results also showed that caregivers experienced burdens related to financial issues and lack of social support. This study recommends mental health professionals provide support, knowledge, and training for caregivers to maintain their psychological well-being.